Helicity correlation of neighboring dihadron - Fei Huang; Tianbo Liu; Yu-Kun Song; Shu-Yi Wei (Physics Letters B)
The spin correlation of final-state hadrons provides a novel platform to explore the hadronization mechanism of polarized partons in unpolarized high-energy collisions. In this work, we investigate the helicity correlation of two hadrons originating from the same single parton. The production of such a dihadron system is formally described by the dihadron fragmentation function, in which the helicity correlation between the two hadrons arise from both the long-distance nonperturbative physics and the perturbative QCD evolution. Beyond the extraction of the dihadron fragmentation function, we demonstrate that it is also a sensitive observable to the longitudinal spin transfer, characterized by the single hadron fragmentation function G1L. This intriguing connection opens up new opportunities for understanding the spin dynamics of hadronization and provides a complementary approach to corresponding studies using polarized beams and targets.